Preparation of Gel Alcohol Flavored with Essential Oils. An Employ of Laboratory Techniques in the Organic Chemistry Study - Guntero, Vanina Alejandra (2017)
The main aim of this work is to teach chemistry through a practical application. In it is described a chemical experiment for high school students. They learn fundamental concepts through the preparation of gel alcohol flavored. The experiment has four stages: search information, cultivation of aromatic plants, extraction of essential oils, and elaboration of gel alcohol. The hydro distillation technique was applied in order to obtain the corresponding essential oil. The aromatic plants used were cloves, lavender, rosemary, salvia and cedron. The essential oils were analyzed by gas chromatography. The experiment demonstrated to the students the application of chemistry for the preparation of personal care products making concepts more tangible than a simple reading.